Female garment workers' understandings of sexually transmitted infections in selected low to middle-income countries: A systematic review - Mahmood, Shakeel (YCAB Publisher & IAKMI SULTRA, 2021)
Objective: This study reviewed the current state of knowledge of female garment workers' (FGWs) personal understandings and their experiences of their human immunodeficiency virus (HIV) experiences in selected low to middle-income countries (LMIC).Methods: Relevant literature on FGWs health on sexually transmitted infections (STIs) and HIV within selected LMIC published between 1988 and 2020 carried out, and a systematic review search technique used, utilizing the PRISMA protocol. Significant and relevant information from selected articles obtained and presented existing literature in the method of new outcomes as well as critically interpret existing outcomes. The themes and keywords were examined in the abstract and title of literature extracted using the aforementioned search engines.Results: Major causes of HIV vulnerability of FGWs are poverty (low wages), gender inequality, drug abuse, multiple sex partners, lack of knowledge on STIs/HIV, low use of condoms, and rape violence found in selected LMIC.Conclusion: For empowering FGWs, health education/workplace intervention is crucial, comprising prevention of sexual harassment, workplace violence (WPV), and intimate partner violence (IPV) related training by government sectors, non-government organizations (NGOs), and civil society. A good surveillance system on key populations, including FGWs, and a good public health system in every country is the key and acts very fast for prevention of STIs and HIV on FGWs and contribute to guide policymakers and researchers and improve FGWs health in LIMC.